PENGARUH TINGKAT LITERASI KEUANGAN TERHADAP PENGELOLAAN KEUANGAN PADA PELAKU UMKM (STUDI KASUS UMKM KERAJINAN TANGAN DI KOTA PEKANBARU) - Fauziah Manurung; Henny Indrawati; Mujiono (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
This study aims to determine the effect of financial literacy on the management of small and medium enterprises in the city of Pekanbaru. The research sample for handicraft SMEs in Pekanbaru city is 62 SMEs and the sample is taken using a purposive sampling technique. The characteristics of the sample are a minimum of five years of business and recorded financial transactions. Data for this study were collected using questionnaires distributed to respondents. The collected data were then analyzed using descriptive analysis and simple linear regression. Based on the results of the study, it shows that financial literacy has a significant effect on the financial management of handicraft SMEs in the city of Pekanbaru. These results indicate that the higher the level of financial literacy, the better financial management. Keywords: Financial Management, Financial LiteracyThis study aims to determine the effect of financial literacy on the management of small and medium enterprises in the city of Pekanbaru. The research sample for handicraft SMEs in Pekanbaru city is 62 SMEs and the sample is taken using a purposive sampling technique. The characteristics of the sample are a minimum of five years of business and recorded financial transactions. Data for this study were collected using questionnaires distributed to respondents. The collected data were then analyzed using descriptive analysis and simple linear regression. Based on the results of the study, it shows that financial literacy has a significant effect on the financial management of handicraft SMEs in the city of Pekanbaru. These results indicate that the higher the level of financial literacy, the better financial management.Keywords: Financial Management, Financial Literacy